Cell wall evolution and diversity - Fangel, Jonatan U.; Ulvskov, Peter; Knox, J. Paul; Mikkelsen, Maria D.; Harholt, Jesper; Popper, Zoë A.; Willats, William G. (Frontiers in Plant Science, 2012)
Plant cell walls display a considerable degree of diversity in their compositions and molecular architectures. In some cases the functional significance of a particular cell wall type appears to be easy to discern: secondary cells walls are often reinforced with lignin that provides durability; the thin cell walls of pollen tubes have particular compositions that enable their tip growth; lupin seed cell walls are characteristically thickened with galactan used as a storage polysaccharide. However, more frequently the evolutionary mechanisms and selection pressures that underpin cell wall diversity and evolution are unclear. For diverse green plants (chlorophytes and streptophytes) the rapidly increasing availability of transcriptome and genome data sets, the development of methods for cell wall analyses which require less material for analysis, and expansion of molecular probe sets, are providing new insights into the diversity and occurrence of cell wall polysaccharides and associated biosynthetic genes. Such research is important for refining our understanding of some of the fundamental processes that enabled plants to colonize land and to subsequently radiate so comprehensively. The study of cell wall structural diversity is also an important aspect of the industrial utilization of global polysaccharide bio-resources.